Origin of the enhanced Nb3Sn performance by combined Hf and Ta doping - Tarantini, C; Kametani, F; Balachandran, S; Heald, SM; Wheatley, L; Grovenor, CRM; Moody, MP; Su, Y-F; Lee, PJ; Larbalestier, DC (Springer Nature, 2021)
In recent years there has been an increasing effort in improving the performance of Nb3Sn for high-field applications, in particular for the fabrication of conductors suitable for the realization of the Future Circular Collider (FCC) at CERN. This challenging task has led to the investigation of new routes to advance the high-field pinning properties, the irreversibility and the upper critical fields (HIrr and Hc2, respectively). The effect of hafnium addition to the standard Nb-4Ta alloy has been recently demonstrated to be particularly promising and, in this paper, we investigate the origins of the observed improvements of the superconducting properties. Electron microscopy, Extended X-ray Absorption Fine Structure Spectroscopy (EXAFS) and Atom Probe Tomography (APT) characterization clearly show that, in presence of oxygen, both fine Nb3Sn grains and HfO2 nanoparticles form. Although EXAFS is unable to detect significant amounts of Hf in the A15 structure, APT does indeed reveal some residual intragrain metallic Hf. To investigate the layer properties in more detail, we created a microbridge from a thin lamella extracted by Focused Ion Beam (FIB) and measured the transport properties of Ta-Hf-doped Nb3Sn. Hc2(0) is enhanced to 30.8 T by the introduction of Hf, ~ 1 T higher than those of only Ta-doped Nb3Sn, and, even more importantly the position of the pinning force maximum exceeds 6 T, against the typical ~ 4.5–4.7 T of the only Ta-doped material. These results show that the improvements generated by Hf addition can significantly enhance the high-field performance, bringing Nb3Sn closer to the requirements necessary for FCC realization.